How much can nuclear energy do about global warming?. (2017) - Berger, André; Blees, Tom; Bréon, Francois-Marie; Brook, Barry W.; Hansen, Philippe; Grover, Ravi B.; Guet, Claude; Liu, Weiping; Livet, Frederic; Nifenecker, Herve; Petit, Michel; Pierre, Gérard; et al.
The framework MESSAGE from the IIASA fulfills the IPCC requirement RCP 2.6. To achieve this, it proposes the use of massive deployment of Carbon Dioxide Capture and Storage (CCS), dealing with tens of billion tons of CO2 . However, present knowledge of this process rests on a few experiments at the annual million tons level. MESSAGE includes three scenarios: 'Supply' with a high energy consumption; 'Efficiency' which implies the end of nuclear energy and the intermediary 'MIX'. We propose, as a variant of the MESSAGE framework, to initiate a sustained deployment of nuclear production in 2020, reaching a total nuclear power around 20, 000 GWe by the year 2100. Our scenarios considerably reduce the interest or necessity for CCS. Renouncing nuclear power requires an energy consumption reduction of more than 40% compared to the 'Supply' scenario, without escaping the need to store more than 15 billion tons of CO2 .